Highly effective dietary inclusion of laurel (Laurus nobilis) leaves on productive traits of broiler chickens - Nihad Abdul-Lateef Ali; Mohammed Baqur Sahib Al-Shuhaib (Acta Scientiarum. Animal Sciences, 2021)
Laurel leaves characterized with interesting antioxidant effects, which have often used to improve the immunity with positive consequences on growth and performance This study was conducted to assess the effect of adding crushed laurel leaves to the diet on the productive traits of broiler chickens. A total of 180 broiler chickens, were randomly assigned to four dietary treatments, with a rate of 45 birds per treatment; each treatment consisted of three replicates. The first treatment, or control, was generated without adding laurel leaves to the diet, second, third, and fourth treatments were generated by adding laurel leaves with amounts of 1, 2, and 3 g kg-1 feed, respectively. Nine productive traits were evaluated in this study, including the average of live body weight, weight gain, feed consumption, feed conversion ratio, percentage of mortality, productive index, length of the villus, depth of crypts, and villus length/crypts length ratio. Results indicated that the addition of laurel leaves led to a significant improvement in all productive traits, signifying highly essential participation of laurel leaves to enhance growth and performance. In conclusion, it can be stated that adding 3 g kg-1 of crushed laurel leaves to the diet can improve the productive traits of broiler chickens.